The Important Role of Pyrolysis and Hydrothermal Carbonization in a Sustainable Circular Bioeconomy: A Brief Literature Review - Jansson, Eira; Kjell, Malin; Ålund, Karin (Studia Ecologiae et Bioethicae, 2024)
This is a brief but focused literature review of articles centered around pyrolysis and hydrothermal carbonization (HTC) using various feedstocks, including residues from industries, agriculture, and landfill waste. The deployment of bio-wastes will be the cornerstone of circular bio-economies in the future. The main emphasis is on gleaning how these two technologies can contribute to a sustainable circular (bio) economy, by understanding the process parameters influencing the quality, type and quantity of the final output. HTC and pyrolysis, it may be undeniably stated, can support the progress towards a clutch of sustainable development goals (SDGs), as they operate right at the confluence of solid waste management and renewable energy production. As mentioned in many of the articles reviewed in this paper, a high process temperature usually results in higher yields of bio-oil and biogas/pyrogas (and thereby less biochar), implying a higher energy recovery. HTC trumps pyrolysis on many counts – economy, energy-efficiency and product (hydrochar) quality. However, pyrolysis is a simpler method to regulate, and pyrochar, has a higher market value vis-à-vis hydrochar. While both these technologies generate valuable end-products regardless of the type of feedstock used; the articles reviewed clearly show that the feedstock does influence the quality of the output and thereby the application to which it can be directed. The review leads to recommendations for future research in collecting data and creating a model to investigate various process parameters. Some of these recommendations are detailed comparative life cycle assessments (LCAs) to study the environmental impacts of technology-choices, , research into tailoring the optimal method and temperature to the feedstock deployed, and comprehensive forecast-based economic analysis of commercial-scale pyrolysis and HTC projects, are called for. As stated at the beginning, this is a brief review, which can also be expanded to take more published articles into its fold.